The future of Northern Ireland: border anxieties and support for Irish reunification under varieties of UKexit. Issue 9 (2nd September 2021) - Garry, John; O'Leary, Brendan; McNicholl, Kevin; Pow, James
ABSTRACT: The paper assesses public attitudes in Northern Ireland towards the potential hardening of the border between Northern Ireland and the Republic of Ireland as a result of the UK's exit from the European Union. It investigates the relationship between border-related anxieties and support for a United Ireland. The study draws on specially designed qualitative and quantitative data, generated from a one-day citizens' assembly and a representative attitude survey. It identifies a group of conditional Catholics who support Irish unity, but only under 'hard exit' conditions.